Optimalisasi Pemasaran Guna Peningkatan Volume Penjualan Pada Kelompok Tani Hutan Di Desa Puspo Kabupaten Pasuruan - Rizcha Oktanza Fabiyola; Dona Wayuning Laily (Universitas 45 Surabaya, 2023)
Community service activities carried out in Puspo Village, Pasuruan Regency were carried out with the aim of helping the Rukun Sejahtera Puspo Forest Farmers Group in overcoming the problem of marketing coffee products. Efforts that can be made in helping the Rukun Sejahtera Puspo Forest Farmer Group are to find optimal marketing methods to increase the volume of coffee sales in Puspo Village. Solutions that can be offered related to marketing methods are by changing conventional marketing methods to more modern marketing methods and paying attention to customer satisfaction to find out how efficient marketing methods are currently used.